Case Report: Severe Hypotonia Without Hyperphenylalaninemia Caused by a Homozygous GCH1 Variant: A Case Report and Literature Review - Chen, Yun; Liu, Kaiyu; Yang, Zailan; Wang, Yaozhou; Zhou, Hao (Frontiers in Genetics, 2022)
Dopa-responsive dystonia (DRD) comprises a group of rare but treatable dystonias that exhibit diurnal fluctuation. The GCH1 gene encodes GTP cyclohydrolase-1 (GTPCH-І), a protein that catalyzes the first rate-limiting step of tetrahydrobiopterin biosynthesis. Pathogenic variants in GCH1 are the most common causes of DRD. However, the autosomal recessive form of DRD caused by homozygous GCH1 variants is very rare. Homozygous GCH1 variants have been associated with two clinically distinct human diseases: hyperphenylalaninemia, and DRD with or without hyperphenylalaninemia. Here, we describe one patient who presented during infancy with severe truncal hypotonia and motor developmental regression but without diurnal fluctuation and hyperphenylalaninemia. Treatment with levodopa/carbidopa resulted in the complete and persistent remission of clinical symptoms without any side effects. This was accompanied by age-appropriate neurological development during follow-up. A homozygous GCH1 variant (c.604G>A/p.V202I) was identified in the patient. To our knowledge, this is the first Chinese case of DRD caused by a homozygous GCH1 variant, thus expanding the spectrum of DRD phenotypes. Autosomal recessive DRD that is associated with homozygous GCH1 variants should be considered in patients with severe truncal hypotonia, with or without diurnal fluctuation, even if there is an absence of limb dystonia and hyperphenylalaninemia.